Private Sector Creditand Economic Growth Nexus in Nigeria: An Autoregressive Distributed Lag Bound Approach - Aliero, Haruna Mohammed; Abdullahi, Yahya Zakari; Adamu, Nasiru (Richtmann Publishing, 2013)
This paper analyses the relationship between private sector credit and economic growth in Nigeria, using time series data forthe period of thirty-seven (37) years (1974-2010). In analyzing the data the paper used Autoregressive Distributed Lag (ARLD)bound F-test for cointegration. The results indicated that a long run equilibrium relationship exists between private sectorcredit and economic growth, when private sector credit was used as dependent variable. However, causality results indicatethat there is no causal relationship between private sector and economic growth in Nigeria. Therefore the empirical findings ofthis research implied that while â€œdemand following hypothesisâ€ prevailed in the long run relationship between private sectorcredit and economic growth in Nigeria, non-causal impact between private sector and economic growth on the other handindicates the prevalence of the Schumpeterian â€œindependent hypothesisâ€ on the Nigerian economy. Finally, the studyrecommends long-term investment loan to the productive private sector in addition to the need for comprehensive policies andstrong legal framework for easy disbursement and quick recovery of private sector credit.